2015
DOI: 10.1007/s11892-015-0604-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Nutrient Sensing Determine How We “See” Food?

Abstract: The ability to "see" both incoming and circulating nutrients plays an essential role in the maintenance of energy homeostasis. As such, nutrient-sensing mechanisms in both the gastrointestinal tract and the brain have been implicated in the regulation of energy intake and glucose homeostasis. The intestinal wall is able to differentiate individual nutrients through sensory machinery expressed in the mucosa and provide feedback signals, via local gut peptide action, to maintain energy balance. Furthermore, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…The cross-sectional nature of the study limits the ability to make D r a f t 16 causal inferences with respect to metabolic and anthropometric predictors of energy intake variables. We also cannot discount the role that diabetes risk factors as inclusion criteria may have had on energy intake; the role of nutrient sensing, particularly with elevated glycemia and insulinemia, may have acted as an extraneous variable influencing appetite and energy intake (Hamr et al 2015). A major strength of the present study is that body composition was measured with MRI, which allowed for the accurate assessment not only of FM and total FFM, but also skeletal muscle mass.…”
Section: R a F Tmentioning
confidence: 97%
“…The cross-sectional nature of the study limits the ability to make D r a f t 16 causal inferences with respect to metabolic and anthropometric predictors of energy intake variables. We also cannot discount the role that diabetes risk factors as inclusion criteria may have had on energy intake; the role of nutrient sensing, particularly with elevated glycemia and insulinemia, may have acted as an extraneous variable influencing appetite and energy intake (Hamr et al 2015). A major strength of the present study is that body composition was measured with MRI, which allowed for the accurate assessment not only of FM and total FFM, but also skeletal muscle mass.…”
Section: R a F Tmentioning
confidence: 97%
“…Gastrointestinal endocrine factors can act separately or in concert with nerve‐mediated mechanisms creating an impressive and complex basis for regulatory actions, not only within the gut itself but also with projections on distant tissues. Eating behaviour is partly regulated by peripheral signals from mechanical and nutrient neurohumoral sensing within the gut with final projections in the central nervous system . Ghrelin is a hormone released mainly from the stomach and is proposed to exert an orexigenic effect, including hunger sensation .…”
Section: Central Obesity and Body Weight Controlmentioning
confidence: 99%
“…The efficacy of this proximal‐to‐distal gut signalling on gut hormone‐releasing cells is partly dependent on the ileocolonic microbial composition determining the degree of conversion from primary conjugated bile acids to absorbable secondary bile acids. Furthermore, recent research has demonstrated numerous specialized nutrient sensors, for example single‐modality sensitive intestinal taste cells, that in parallel with metabolic regulation at the organ level probably also influence central feed‐forward hedonic mechanisms and food intake behaviour . However, many of these specific sensing mechanisms have so far only been tested at an experimental level and await confirmation in humans.…”
Section: Central Obesity and Body Weight Controlmentioning
confidence: 99%
“…Whilst there is increasing evidence that changes in intestinal immune-signalling convey shifts in gut-facilitated energy homeostasis, the majority of recognised axial effects on energy homeostasis are a consequence of neural and hormonal gut-derived signals, as the GIT possesses over 500 million neurons and is capable of producing an array of hormones (Monje, 2017 ). Hence, due to the large degree of innervation supplying the GIT, preabsorptive foodstuffs can initiate signals to the CNS regarding macronutrient content and caloric value through individualised nutrient-specific sensory mechanisms located throughout the GIT (Hamr et al, 2015 ). These signals are subsequently conveyed to various regions of the brain, such as the brainstem and hypothalamus.…”
Section: The Gut-brain Axis: Connections From the Gut To The Brainmentioning
confidence: 99%